2002
DOI: 10.1001/archopht.120.7.933
|View full text |Cite
|
Sign up to set email alerts
|

Combined Plaque Radiotherapy and Transpupillary Thermotherapy for Choroidal Melanoma

Abstract: To evaluate tumor control and treatment complications following plaque radiotherapy combined with transpupillary thermotherapy for choroidal melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 27 publications
4
88
1
3
Order By: Relevance
“…Various materials for delivering radiation have been investigated, beginning with radon in the 1930s by Moore. 28 Iodine-125 is currently the most commonly used isotope for plaque radiotherapy of choroidal melanomas, 29,30 although cobalt-60, ruthenium-106, iridium-192, strontium-90, and palladium-103 have also been used. Modern techniques for plaque brachytherapy involve suturing a shielded plaque containing seeds of the radioactive isotope to the sclera.…”
Section: Radiotherapymentioning
confidence: 99%
“…Various materials for delivering radiation have been investigated, beginning with radon in the 1930s by Moore. 28 Iodine-125 is currently the most commonly used isotope for plaque radiotherapy of choroidal melanomas, 29,30 although cobalt-60, ruthenium-106, iridium-192, strontium-90, and palladium-103 have also been used. Modern techniques for plaque brachytherapy involve suturing a shielded plaque containing seeds of the radioactive isotope to the sclera.…”
Section: Radiotherapymentioning
confidence: 99%
“…Combined plaque radiotherapy and TTT has been shown to provide excellent control of intraocular tumors. Shields et al (3) and Bartlema et al (4) reviewed 270 and 50 cases, respectively, and found recurrence rates at 5 years after treatment of up to 3%. However, neither study found any cases of extraocular extension.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary extraocular extension following conservative treatment of CM is extremely rare (3) and usually small in size. Historically, this pre sentation has been associated with surgical resection and TTT without adjuvant brachytherapy thought to result in insufficient elimination of tumor margins and intrascleral tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have noted significant enhancement of radiation effects from heat in animal models of uveal melanoma. 13 Several investigators [14][15][16][17] have used a combination of this form of laser-induced hyperthermia plus brachytherapy to treat uveal melanomas. In a recent study, Shields and colleagues 17 noted increased tumor control, nearing that achieved with charged particles when this form of laser is used after I-125 brachytherapy.…”
Section: Discussionmentioning
confidence: 99%